Penerapan budaya disiplin guru dalam meningkatkan kualitas pembelajaran siswa di MTsN 1 Kota Kediri - Dhorifah, Ani Nurus (Maliki Interdisciplinary Journal, 2024)
This research aims to investigate the implementation of a culture of discipline by teachers as a strategy to improve the quality of student learning in an educational environment. By combining qualitative and quantitative approaches, this study documents the pedagogical practices that teachers use to establish and maintain a disciplinary culture in the classroom. Through direct observations, interviews with teachers, and student surveys, data is collected and analyzed to identify the effectiveness of the strategies implemented by teachers. The research results show that implementing a disciplinary culture has a significant positive impact on various aspects of student learning, including concentration, discipline, active participation, and academic achievement. Apart from that, this research also reveals supporting factors and obstacles in implementing a disciplinary culture, as well as strategies that can be implemented to overcome these challenges. Practical implications of these findings include recommendations for the development of teacher training that strengthens classroom management skills and fosters a culture of discipline. Additionally, this article also suggests directions for further research in this area, including cross-cultural research to understand more about the implementation of disciplinary culture in various educational contexts. Thus, this research makes an important contribution in enriching our understanding of the role of disciplinary culture in improving the quality of student learning and supporting sustainable educational development efforts.